Mobilizing young voters with short text messages in nationwide field experiments - Salomo Hirvonen; Maarit Lassander; Lauri Sääksvuori; Janne Tukiainen (Aboa Centre for Economics (ACE), 2024)
This paper examines how randomized get-out-the-vote (GOTV) appeals affect inequalities in voting and voters' turnout decisions transmit in social networks in high salience elections. Moreover, we study the persistence of GOTV mobilization effects across successive elections using a linked dataset covering electronic voting records and randomized treatment assignments across two consecutive elections. We find that receiving a text message reminder before the Finnish 2023 parliamentary elections mainly mobilized young voters with low predicted probability to vote, implying that our intervention reduced existing social inequalities in voting within the target group of young voters. We find that the previously documented remarkably large within household spillovers in voting largely generalize from low salience elections to high salience elections and document that over 100 percent of the direct treatment effect spilled over to untreated household members. We do not find any evidence for the persistence of the treatment received in the previous elections nor of interaction effects between the two experiments. This suggests that the effects of GOTV appeals are only temporary but can be repeated through new appeals across the elections.
Keywords: C93; D72; 330; Field experiments; Dynamic effects; Get-out-the-vote; Inequality in voting; Nudging; Spillover effects; Voter turnout